2004
DOI: 10.1111/j.1600-0897.2004.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Killer Inhibitory Receptor CD158a Overexpression Among Natural Killer Cells in Women With Endometriosis is Undiminished by Laparoscopic Surgery and Gonadotropin Releasing Hormone Agonist Treatment*

Abstract: Increased percentage of CD158a(+)NK cells in peripheral blood from women with endometriosis was undiminished by laparoscopic surgery and GnRHa treatment; the persistence of CD158a(+)NK cell excess is probably related to NK cell suppression in endometriosis. This overexpression may represent a risk factor for development of endometriosis and its recurrence after treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 28 publications
(30 reference statements)
2
40
0
Order By: Relevance
“…This suggests that KIRs expressed on NK cells can respond to their HLA class I ligands on eutopic endometrium [39][40][41]. It was also reported that progesterone induces HLA class I mRNA expression by cultured cells from secretory endometrium [51].…”
Section: Hla Class Iamentioning
confidence: 88%
See 3 more Smart Citations
“…This suggests that KIRs expressed on NK cells can respond to their HLA class I ligands on eutopic endometrium [39][40][41]. It was also reported that progesterone induces HLA class I mRNA expression by cultured cells from secretory endometrium [51].…”
Section: Hla Class Iamentioning
confidence: 88%
“…In women with endometriosis, expression of inhibitory killer immunoglobulin-like receptors on NK cells from PB and PF is significantly upregulated compared with the level of expression in women without endometriosis [39][40][41], indicating a decrease of NK cell activity and cytotoxicity for endometriotic cells.…”
Section: Nk Cells and Endometriosismentioning
confidence: 94%
See 2 more Smart Citations
“…HOXA-10 expression has been also found to be markedly decreased in endometriosis in comparison to normal endometrium [45] . Granzyme and perforin play an important role in NK-mediated cytolysis, where the process is disturbed in endometriosis [46] , while during labor NK cell activity growth is observed in endometrium [47] . The HOXA-10 overexpression observed during tubal rupture by Salih and Taylor might be related to the growing immune cytotoxic activity in the course of tubal rupture described in the present study.…”
Section: Discussionmentioning
confidence: 99%